2020
DOI: 10.1038/s41598-020-76244-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for a future COVID-19 wave: insights and limitations from a data-driven evaluation of non-pharmaceutical interventions in Germany

Abstract: To contain the COVID-19 pandemic, governments introduced strict Non-Pharmaceutical Interventions (NPI) that restricted movement, public gatherings, national and international travel, and shut down large parts of the economy. Yet, the impact of the enforcement and subsequent loosening of these policies on the spread of COVID-19 is not well understood. Accordingly, we measure the impact of NPIs on mitigating disease spread by exploiting the spatio-temporal variations in policy measures across the 16 states of Ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 19 publications
1
41
0
Order By: Relevance
“…We included two observational 43 44 and thirteen modeling studies 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 .…”
Section: Findings Of Included Studies On Effectiveness (N=65)mentioning
confidence: 99%
See 1 more Smart Citation
“…We included two observational 43 44 and thirteen modeling studies 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 .…”
Section: Findings Of Included Studies On Effectiveness (N=65)mentioning
confidence: 99%
“…Lifting bordure closure in Germany resulted in minimal to no effect in increasing the daily cases over a 90-day period while lifting contact restriction policies resulted in the highest increase. 47 …”
Section: Findings Of Included Studies On Effectiveness (N=65)mentioning
confidence: 99%
“…For example, contact restriction may be an effective control measure. 17 The second aspect of control measures is whether the interregional mobility restriction can reduce the national total number of infections. Distinguishing between the short-and long term control measures is important, and the fundamental goal should be toward reducing the overall epidemic size.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Effective control measures that prevent spatial spread of SARS-CoV-2 are urgently demanded, and how NPIs such as travel restrictions and social distancing mitigate the epidemic must be investigated. [17][18][19][20][21][22][23][24][25][26][27] The present study aims to provide meaningful implications for combating the COVID-19 pandemic through interregional mobility restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…We found that gathering restrictions and facial coverings significantly changed the pandemic trajectory in both waves, and gathering restrictions include both gathering cancellation 29 and closure of non-essential businesses [30][31][32] . The significant effects of these measures might be due to the virus most commonly spread through droplets or aerosols among people who were in close contact 33 .…”
Section: Effect Of Integrated Covid-19 Vaccination and Npismentioning
confidence: 91%